2018
DOI: 10.1080/00015385.2018.1440905
|View full text |Cite
|
Sign up to set email alerts
|

QT prolongation and sudden cardiac death risk in hypertrophic cardiomyopathy

Abstract: Prolonged QTc was a risk factor for SCD and death even when controlling for typical risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
3
9
1
2
Order By: Relevance
“…Several mechanisms have been proposed to explain these observations, including concomitant atrial cardiomyopathy, atrial torsades de pointes, atrio‐ventricular dyssynchrony secondary to QTc prolongation, and inflammatory reaction in both the atria and ventricles . Interestingly, in a series of over 1600 HCM patients from the Mayo Clinic, the authors found that the cut‐off value of QTc that could significantly predict death or SCD was 450 ms, almost identical to the value we calculated for predicting AF ablation outcome in HCM patients …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Several mechanisms have been proposed to explain these observations, including concomitant atrial cardiomyopathy, atrial torsades de pointes, atrio‐ventricular dyssynchrony secondary to QTc prolongation, and inflammatory reaction in both the atria and ventricles . Interestingly, in a series of over 1600 HCM patients from the Mayo Clinic, the authors found that the cut‐off value of QTc that could significantly predict death or SCD was 450 ms, almost identical to the value we calculated for predicting AF ablation outcome in HCM patients …”
Section: Discussionsupporting
confidence: 68%
“…10,16 Interestingly, in a series of over 1600 HCM patients from the Mayo Clinic, the authors found that the cut-off value of QTc that could significantly predict death or SCD was 450 ms, almost identical to the value we calculated for predicting AF ablation outcome in HCM patients. 17…”
Section: Qtc Interval Prolongation and Arrhythmia Recurrencementioning
confidence: 99%
“…T waves can be helpful in a variety of pathologies: as an example, tall T waves in anterior chest lead III, aVR, and V1 with a negative QRS complex may suggest acute myocardial ischemia 10 . QT interval measures myocardial depolarization and repolarization time, while shortening or prolongation of QT interval is associated with an increased risk for arrhythmias and sudden cardiac death (SCD) 11,12 . Abnormal PR interval is a risk factor for atrial fibrillation and heart block 13 .…”
mentioning
confidence: 99%
“…SCD from the former is partly accounted for by the increase in fluid, electrolytes, and metabolites, while that from the latter may represent intradialytic risk of arrhythmia and the potential for subsequent fatal event during and immediately after a dialysis session. Recent reports showing the strong relationship between QTc interval and SCD in hypertrophic cardiomyopathy [18, 19] and the impact on QTc interval of vascular calcification which becomes more severe as the stage of CKD progresses [20], allowed us to believe the importance of QTc interval as risk assessment for SCD in HD patients.…”
Section: Discussionmentioning
confidence: 99%